The Determination of the Asynchronous Traction Motor Characteristics of Locomotive - Pavel Grigorievich Kolpakhchyan; Alexey Rifkatovich Shaikhiev; Alexander Evgenievich Kochin; Konstantin Stepanovich Perfiliev; Jan Otypka; Andrey Valerievich Sukhanov (Advances in Electrical and Electronic Engineering, 2017)
The article deals with the problem of the locomotive asynchronous traction motor control with the AC diesel-electric transmission. The limitations of the torque of the traction motor when powered by the inverter are determined. The recommendations to improve the use of asynchronous traction motor of locomotives with the AC diesel-electric transmission are given.